ELISIONS CORRESPONDENCE TO SPEECH RATE IN EMINEMS OFFENDED SUB-VERSES - HENDY ANDANA, ADITYA (LANGUAGE HORIZON, 2018)
Abstrak Pada konteks wicara dalam kehidupan sehari - hari, produktivitas elision pada umumnya sejalan dengan kecepatan ucap. Namun, pada konteks wicara dalam rap, produktivitas elision dapat disebabkan oleh kecepatan ucap atau dialek bahasa Inggris khas masyarakat Afrika-Amerika yang juga disebut sebagai Black English Vernacular atau BEV. Penelitian ini dimaksudkan untuk menjawab isu tersebut. Meneliti lagu rap dari Eminem yang berjudul Offended, tiga bait dalam lagu tersebut dibagi menjadi empat sub-bait. Empat sub-bait tersebut kemudian diurutkan berdasarkan kecepatan ucap masing ? masing. Total jumlah elision pada ke-empat bait tersebut kemudian dihitung dan dibandingkan satu sama lain. Hasilnya, elision dalam sub-bait dari lagu Offended tidak dipengaruhi oleh kecepatan ucap, namun oleh dialek. Berdasarkan pola dari elision tersebut, ditemukan bahwa lebih dari 80 persen didasari oleh BEV. Pada proses selanjutnya, fonem dengan jumlah elision terbanyak beserta implikasi yang menyertai, dikaji lebih dalam. Kata kunci: Black EnglishVernacular, Elision, Eminem, Rap, Fonem, Kecepatan Ucap Abstract As productivity of elisions is generally corresponds to speech rate in normal speech, it becomes a question in whether it works in the same way in raps. Ambivalence appears as the cause of elisions in raps possibly comes from speech rate or BEV, which is also known as Black English Vernacular, given to the fact that raps are one of the products of African American culture. Using Eminems song entitled Offended, this study delved into this issue. Four sub-verses were extracted from three verses of the song. Later, the sub-verses were ranked based on their speech rate. Every sub-verse was counted for its numbers of elisions. Subsequently, they were compared to one another. The result showed that the productivities of elisions in the Eminems Offended sub-verses were not affected by speech rate, but a dialect. Based on the patterns of the elisions, it was found that more than 80 percent of elisions were underlain by BEV. In further examination, the most elided vowel and consonant phoneme sounds and their implications ensuing for their predominant appearance were included. Keywords: Black English Vernacular, Elision, Eminem, Rap, Phoneme, Speech Rate